Intravesical bacillus Calmette–Guérin instillation in non‐muscle‐invasive bladder cancer: A review. (25th July 2017) - Saluja, Manmeet; Gilling, Peter
Abstract: Intravesical bacillus Calmette–Guérin has been the standard of care for high‐risk non‐muscle‐invasive bladder cancer for 40 years. It remains one of the most successful immunotherapies ever used. Bacillus Calmette–Guérin shows superior efficacy to alternative intravesical treatments, and has an established role in reducing both recurrence and progression in non‐muscle‐invasive bladder cancer. It remains relatively safe, and has acceptable tolerability of both local and systemic side‐effects. The present review provides insights into the role of bacillus Calmette–Guérin compared with alternative treatments both in primary and refractory settings.